ICTs for rural development: potential applications and barriers involved - Anastasia Stratigea (Netcom)
Rural policy nowadays is at the heart of the policy discussion in many countries all over the world, in the effort to address and effectively support the specific needs and opportunities of rural places and their population in the new era. Along these lines, the focus of the present paper is twofold: on the one hand it attempts to shed light on the role of ICTs and their applications as enabling tools empowering rural development; while on the other hand it explores the barriers appearing towards the adoption and use of ICTs in rural regions. In such a context, it firstly places emphasis on the evolving new rural development paradigm. Then, the range and potential of ICTs applications is explored, that can serve the implementation of the new policy paradigm in rural regions. It follows a discussion on the steps that are needed in order to develop value-added ICTs applications in rural regions and the barriers appearing in the adoption and use of ICTs in these regions. Finally, are presented some issues of policy concern in respect to the adoption and use of ICTs in a rural development perspective.